Effects of extreme deposition rate on the microstructure evolution of additive friction stir deposited AA6061 alloy - Lu Jiang; Ramesh Varma; Mahendra Ramajayam; Thomas Dorin; Matthew Robert Barnett; Daniel Fabijanic (Additive Manufacturing Letters)
Additive manufacturing (AM) using additive friction stir deposition (AFSD) offers unique advantages over traditional liquid-solid state transitions, notably the ability to plasticise materials through frictional and deformation heat and build a bulk deposit via discrete layers without melting. Although inherently a large-scale and high deposition rate process, the boundaries of deposition rates have not been explored. In this work, we explored a deposition rate 4–29 times faster than typical for aluminium AFSD processing. The microstructure analyses of the deposited AA6061 alloys reveal a distinct grain structure and precipitation between the slow and fast depositions, attributed to the varied thermal and mechanical histories stemming from differences in tool velocity. The AFSD process also effectively refines the constituent intermetallic phases, resulting in more uniform sizes due to high temperatures and strains experienced during deposition. Energy consumption analysis revealed significant efficiency improvement associated with the fast deposition.